Profitabilitas pada bank umum syariah dan peran biaya intermediasi, capital adequacy ratio, pembiayaan mudharabah, financing to deposit ratio, dan dana pihak ketiga - Affandy, Gabriell Lisna; Arinta, Yusvita Nena (Journal of Accounting and Digital Finance, 2022)
This study aims to determine the effect of bank intermediation costs, capital adequacy ratio, mudharabah financing, financing-to-deposit ratio, and third-party funds on profitability in Islamic commercial banks for the 2016-2020 period. This research type is quantitative, while the analysis method uses multiple linear regression. The results of this study indicate that intermediation costs significantly positively affect profitability (return on assets). In contrast, the capital adequacy ratio, mudharabah financing, financing-to-deposit ratio, and third-party funds do not affect the profitability of Islamic commercial banks.